Hubungan ASI Eksklusif, Makanan Pendamping ASI, Penyakit Infeksi dengan Kejadian Wasting pada Balita: Cross-Sectional Study: Correlation between Exclusive Breastfeeding, Complementary Feeding, Infectious Disease with Wasting among Toddlers: a Cross-Sectional Study - Intiyati, Ani; Putri, Rany Dwi Yuliana; Edi, Imam Sarwo; Taufiqurrahman, Taufiqurrahman; Soesanti, Inne; Pengge, Nuning Marina; Shofiya, Dian (Universitas Airlangga, 2024)
Background: Wasting, an acute nutritional deficiency, is assessed using weight-for-height with a z-score of <-2SD from growth standards. The prevalence of wasting in Puskesmas Kendit is 14.31%, with Kukusan Village at 29%. Objectives: This study examined the correlation between exclusive breastfeeding, Complementary Feeding (CF), infectious diseases, and wasting in young children. Methods: Conducted with a cross-sectional design, the study sampled 51 toddlers through simple random sampling and analyzed the data using Spearman's correlation. Results: Findings revealed no significant correlation between exclusive breastfeeding and wasting (p-value=0.105). However, there was a significant correlation between CF and wasting (p-value=0.026). Nutrient intake, including energy (p-value<0.001), protein (p-value<0.001), fat (p-value=0.002), and carbohydrates (p-value=0.025), was significantly correlated with wasting, as was the presence of infectious diseases (p-value=0.001). Conclusions: While exclusive breastfeeding tends to reduce wasting, appropriate CF and adequate intake of energy, protein, fat, and carbohydrates are associated with a lower prevalence of wasting. Recommended actions include improving exclusive breastfeeding practices, enhancing the quality of CF, and increasing preventive measures for infectious diseases.